Doxycycline-Encapsulated Nanotube-Modified Dentin Adhesives. (December 2014) - Feitosa, S.A.; Palasuk, J.; Kamocki, K.; Geraldeli, S.; Gregory, R.L.; Platt, J.A.; Windsor, L.J.; Bottino, M.C.
This article presents details of fabrication, biological activity ( i.e., anti–matrix metalloproteinase [anti-MMP] inhibition), cytocompatibility, and bonding characteristics to dentin of a unique doxycycline (DOX)–encapsulated halloysite nanotube (HNT)–modified adhesive. We tested the hypothesis that the release of DOX from the DOX-encapsulated nanotube-modified adhesive can effectively inhibit MMP activity. We incorporated nanotubes, encapsulated or not with DOX, into the adhesive resin of a commercially available bonding system (Scotchbond Multi-Purpose [SBMP]). The following groups were tested: unmodified SBMP (control), SBMP with nanotubes (HNT), and DOX-encapsulated nanotube-modified adhesive (HNT+DOX). Changes in degree of conversion (DC) and microtensile bond strength were evaluated. Cytotoxicity was examined on human dental pulp stem cells (hDPSCs). To prove the successful encapsulation of DOX within the adhesives—but, more important, to support the hypothesis that the HNT+DOX adhesive would release DOX at subantimicrobial levels—we tested the antimicrobial activity of synthesized adhesives and the DOX-containing eluates against Streptococcus mutans through agar diffusion assays. Anti-MMP properties were assessed via β-casein cleavage assays. Increasing curing times (10, 20, 40 sec) led to increased DC values. There were no statistically significant differences ( p > .05) in DC within each increasing curing time between the modified adhesives compared to SBMP. No statistically significant differences in microtensile bond strength were noted. None of the adhesives eluates were cytotoxic to the human dental pulp stem cells. A significant growth inhibition of S. mutans by direct contact illustrates successful encapsulation of DOX into the experimental adhesive. More important, DOX-containing eluates promoted inhibition of MMP-1 activity when compared to the control. Collectively, our findings provide a solid background for further testing of encapsulated MMP inhibitors into the synthesis of therapeutic adhesives that may enhance the longevity of hybrid layers and the overall clinical performance of adhesively bonded resin composite restorations.